(untitled) (Journal of Artificial Intelligence Research, 2023)
In recent years, the integration of Artificial Intelligence (AI) into Project Portfolio Management (PPM) has emerged as a transformative strategy for organizations seeking to enhance strategic alignment and optimize resource distribution. This paper analyzes the application of AI in PPM, focusing on how AI-driven data analysis can facilitate decision-making processes that align projects with strategic goals. By utilizing machine learning algorithms, organizations can analyze vast amounts of data to predict project outcomes, assess risks, and allocate resources more efficiently. Furthermore, AI can improve stakeholder engagement and enable real-time adjustments in project execution, fostering a more dynamic and responsive project environment. The findings illustrate that organizations adopting AI in their PPM practices are better positioned to achieve their strategic objectives and improve overall project performance.